Energy price shocks, monetary policy and inequality - Alina Bobasu; Michael Dobrew; Amalia Repele (European Central Bank (ECB), 2024)
We study how monetary policy shapes the aggregate and distributional effects of an energy price shock. Based on the observed heterogeneity in consumption exposures to energy and household wealth, we build a quantitative small open-economy HANK model that matches salient features of the Euro Area data. Our model incorporates energy as both a consumption good for households with non-homothetic preferences as well as a factor input into production with input complementarities. Independently of policy energy price shocks always reduce aggregate consumption. Households with little wealth are more adversely affected through both a decline in labor income as well as negative direct price effects. Active policy responses raising rates in response to inflation amplifies aggregate outcomes through a reduction in aggregate demand, but speeds up the recovery by enabling households to rebuild wealth through higher returns on savings. However, low-wealth households are further adversely affected as they have little savings to rebuild wealth from and instead loose due to further declining labor income.
Keywords: E52; F41; Q43; 330; energy prices; open economy model; heterogeneous agents; monetarypolicy; non-homothetic preferences